1990
DOI: 10.3109/02699209008985484
|View full text |Cite
|
Sign up to set email alerts
|

Speech addressed to hearing-impaired children by their mothers

Abstract: In this cross-sectional study, some characteristics of the maternal language of a large group of hearing-impaired children are described (n = 74). The children had mean bilateral sensori-neural hearing loss of 25-123 dB HL in the better ear; they were monolingual, suffered no additional handicaps, and at the time of the study were aged 3-7 years old. The language data reported here were obtained by transcribing video-recorded play sessions. Both quantitative and syntactic analyses were applied to the maternal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…For example, Cross et al (1980) reported that many dimensions of hearing mothers' input were related to children's MLU. In addition, Gallaway et al (1990) found that the MLU of hearing mothers was highly correlated with deaf children's MLU. The current study is the first to show that mothers' input is also different for deaf children at different levels of vocabulary development.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cross et al (1980) reported that many dimensions of hearing mothers' input were related to children's MLU. In addition, Gallaway et al (1990) found that the MLU of hearing mothers was highly correlated with deaf children's MLU. The current study is the first to show that mothers' input is also different for deaf children at different levels of vocabulary development.…”
Section: Discussionmentioning
confidence: 99%